A RESEARCH AND DEVELOPMENT STUDY OF A RESISTANCE EXERCISE PROGRAM WITH ELASTIC BAND COMBINED WITH SOCIAL SUPPORT FOR OLDER ADULTS AFTER TOTAL KNEE ARTHROPLASTY - Deedpin, Salinthip; Sasat, Siriphan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
Abstract This research and program development is part of a thesis submitted titled "The Effect of Progressive Resistance Exercise with Rubber Chain Program and Social Support on Knee Range of Motion and Quadriceps Muscle Strength in Older Persons After Total Knee Arthroplasty." The objective is to develop and implement a progressive resistance exercise program using rubber chains and social support to improve knee range of motion and quadriceps muscle strength in older persons following total knee arthroplasty. A developmental approach was used to tailor the program to patients’ needs, ensuring effectiveness and feasibility by integrating theoretical and practical elements. The program development process was divided into three phases: 1) problem identification and literature review, 2) program design and development, and 3) program implementation with a sample of ten older persons who had undergone total knee arthroplasty at Police General Hospital. The instruments used included the exercise program (comprising the developed program and teaching media), a knee range of motion measurement tool, a quadriceps muscle strength evaluation form, and a satisfaction questionnaire assessing usability, practicality, safety, and overall satisfaction. The program and teaching media were evaluated by five experts for content validity in terms of appropriateness, continuity, and linguistic accuracy, meeting the standard criteria (CVI ≥ 0.80). Descriptive statistics (percentages, means, and standard deviations) were used for data analysis. The program’s results were well-received, with average scores of 4.73 (±0.45) for participation convenience, 4.87 (±0.35) for practical applicability, 4.60 (±0.49) for safety, and 4.80 (±0.40) for overall satisfaction. These findings underscore the program’s capacity to enhance the physical and emotional recovery of older patients, supporting its appropriateness and effectiveness for future large-scale implementation. Keywords: Progressive resistance exercise, social support, knee range of motion, quadriceps muscle strength.